PENGARUH FAKTOR FUNDAMENTAL TERHADAP RETURN SAHAM DI PT.BURSA EFEK JAKARTA - Taufik Taufik (Program Studi Magister Manajemen FE Unsri, 2009)
This research is aimed to investigate the influence of Internal Fundamental factors i.e. Earning Per Share (EPS), Debt to Equtiy (DER), Dividend Cash Payout Ratio (DPR) and External Fundamental factors i.e. exchange rate (US / IDR), Inflation rate and Interest rate firm stock return of manufacturing sector of 2001 – 2006 at the Jakarta Stock Exchange. The sample used in this research is Purposive sampling. Of 157 firms, only 25 firms can be taken out as samples in this research. Linier Regression was implemented in this research to see the influence of those variables mentioned above to firm capital structure.It was found that only EPS and DPR have positive and significant impact on firm stock return. The other fundamental variables i.e. Debt to Equtiy (DER), exchange rate (US / IDR), Inflation rate and Interest rate has negative and insignifant have negative and insignificant influence on firm stock return.The result also shows that 62,54% of fundamental factors influences firm stock return of manufacturing sector of 2001 – 2006 at the Jakarta Stock Exchange.Since this research is limited to manufacturing sector, further research is recommended to include other firm sectors listed at the Indonesian Stock Exchange and include other firm sectors .Keywords : Stock return return, Earning per Share, Debt to Equity Ratio, Dividend Cash payout ratio, Exchange rate (US / IDR), Inflation rate, Interest rate